Immobilized microalgae for anaerobic digestion effluent treatment in a photobioreactor-ultrafiltration system: Algal harvest and membrane fouling control. (November 2018) - Xie, Binghan; Gong, Weijia; Yu, Huarong; Tang, Xiaobin; Yan, Zhongsen; Luo, Xinsheng; Gan, Zhendong; Wang, Tianyu; Li, Guibai; Liang, Heng
Graphical abstract: Highlights: The PBR-UF was used for algal cultivation, harvest, and ADE purification. Bacteria-algae symbiosis enhanced removals of organics and nutrients in PBRs. Immobilized algal beads avoided cells lysis in the UF filtration. Cake layer in ICV + PAC served a filter layer to alleviate membrane fouling. The EEM-PARAFAC approach was used for fluorescent organics degradation analysis. Abstract: A photobioreactor (PBR) coupled with ultrafiltration (UF) system was developed with goals of microalgae cultivation, harvest, and membrane fouling control in the anaerobic digestion effluent purification. Firstly, three-sequencing batch PBRs were started-up with suspended Chlorella vulgaris ( C. vulgaris, SCV), immobilized C. vulgaris (ICV) and immobilized C. vulgaris with powdered activated carbon (ICV + PAC). The results exhibited high DOC degradation (66.61%–84.35%) and completely nutrients (nitrogen and phosphorus) removals were attained in PBRs. This indicated bacterial-microalgal consortiums enhanced biodegradation and PAC adsorption accelerated photodegradation. During the microalgae harvest by UF, immobilized microalgae beads protected cells integrity with less debris and intracellular/extracellular organic matters lysis. Moreover, the cake layer in ICV + PAC could even serve as a dynamic layer to entrap the residual pollutants and control membrane fouling. Hence, membrane fouling mitigation and ADE purification were realized during the microalgae harvest process in the ICV + PAC.